A Governor Lamented After: Governor of Van Âli Bey - Sadık Emre Karakuş (Tarih Dergisi)
In this article, the biography, governorship and the tragic process leading to the assassination of Âli Bey, who was assassinated by Armenian gangsters on September 23, 1907, right after his appointment as Governor of Van, are discussed. Born in 1861 in Edirne, Âli Bey, who was a member of the Court of Appeals, was appointed as the Governor of Van on December 17, 1906. Taking office at a time when law and order in the region was not fully established, he endeavored to establish state order in the region at a time when missionaries and consuls were constantly active in the region by addressing many issues ranging from military and civil servant appointments to tribal problems, from the fight against Armenian gangs to tax problems in order to establish security and safety. However, he was dismissed from office on September 5, 1907, about nine months after his appointment with different opinions. The people of Van took to the streets and sent telegrams to the Yıldız Palace to demand the reinstatement of their governor, who had not even completed a year in office, but the result did not change. Having appeased the locals, Mr. Âli Bey left Van for Istanbul by sea via Batumi. However, he was killed in an armed attack by Armenian terrorists in Batumi. His body had to be buried in Sinop, not in Istanbul, in order not to cause outrage. It is much rarer for a lament to be sung in the name of a governor, and the folk song “Ali Pasha’yı Vurdular” (They Shot Ali Pasha) was collected from the Van region in the aftermath of these events. What is known about him in oral and written literature consists of statements that do not show integrity; people, names, titles, dates and events, especially Âli Bey, are mixed up and there is a lack of information on many issues. In this study, on the other hand, an effort has been made to correct misinformation and illuminate unknown aspects of the subject through Ottoman archival documents. The result is that even though a governor who tried to do his duty properly was accused and victimized in many respects, his name is unforgettable in the memory of the people and his exemplary story is a lesson in administrative, political and ethnographic terms.